2013
DOI: 10.1038/bjc.2013.624
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type XI α1 facilitates head and neck squamous cell cancer growth and invasion

Abstract: Background:Although it is well established that the extracellular matrix affects tumour progression, not much is known about the various components and their effect on head and neck squamous cell carcinoma (HNSCC) progression. Levels of collagen type XI α1 (colXIα1), a minor fibrillar collagen, have been shown to be increased in tumour compared with normal tissue in several cancers, including colorectal, breast, and non-small cell lung cancer. Currently, the functional significance of colXIα1 is not understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 31 publications
2
37
0
3
Order By: Relevance
“…This finding was confirmed by another study in which colXIα1 was upregulated by an average of 6.63 fold in HNSCC tumors versus normal adjacent tissue 40 . An additional study demonstrated a 7.5-fold increase in colXI α1 mRNA levels in metastatic HNSCC tumors compared to non-metastatic tumors 41 .…”
Section: Dysregulation Of Collagen Xiα1 In Cancersupporting
confidence: 67%
See 2 more Smart Citations
“…This finding was confirmed by another study in which colXIα1 was upregulated by an average of 6.63 fold in HNSCC tumors versus normal adjacent tissue 40 . An additional study demonstrated a 7.5-fold increase in colXI α1 mRNA levels in metastatic HNSCC tumors compared to non-metastatic tumors 41 .…”
Section: Dysregulation Of Collagen Xiα1 In Cancersupporting
confidence: 67%
“…ColXIα1 siRNA-mediated knockdown in both ovarian cancer cell lines and HNSCC cell lines significantly suppressed invasion and slowed proliferation. This effect was not observed when normal, non-cancerous cells were transfected with colXIα1 siRNA, further confirming its potential as a therapeutic target 28,40 . In the ovarian cancer cell lines, colXIα1 knockdown was associated with decreased matrix metalloproteinase (MMP) 3 mRNA expression and activity.…”
Section: Colxiα1 As a Therapeutic Targetmentioning
confidence: 74%
See 1 more Smart Citation
“…[18][19][20] For instance, in human acute lymphocytic leukemia, the expression levels of miR-15a and miR-16-1 are decreased; 21,22 in lung cancer, let-7 is downregulated, whereas miR-17-92 is upregulated; 23 in Burkitt's lymphoma, expression level of miR-155 is increased; 24 in esophageal cancer, miR-103 and miR-107 expression levels are increased; 25 in liver cancer, miR-21 expression level is increased. 26 The important roles of those miRs with altered expression have further been revealed, which forms the basis of their applications in clinical tumor treatments. 24,27 MiR played its role on the target gene through two ways, one was completely complementary pairing with the target gene that might lead to the degradation of the mRNA of the target gene and the other was incompletely complementary pairing with the target gene that might lead to translation inhibition of the target gene.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of COL11A1 are also associated with type II Stickler syndrome and Marshall syndrome (17,18). In regard to tumor formation and development, COL11A1 was reported to promote tumor progression in ovarian cancer, and head and neck squamous cell cancer (HNSCC) (19)(20)(21) (22,23). However, the role of COL11A1 in NSCLC progression and relapse remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%